Contactless Forcing Schemes in Brake Devices of Asynchronous Motors - V. V. Solencov; V. V. Brel (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper contains commonly used and newly developed contactless forcing schemes in brake devices of asynchronous motors. Advantages and drawbacks of various contactless forcing schemes are presented in the paper. Conclusions are made in respect of prospective directions concerning development of contactless forcing schemes in brake devices.